Identification, Antimicrobial Sensitivity and Molecular Detection of Staphylococcus aureus and Staphylococcus pseudintermedius Isolated from Ear Infections of Canines - Vanisree, Yeleswarapu; Filia, Gursimran; Chandra, Mudit; Chabra, Sushma (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was undertaken to identify by molecular detection and investigate the antimicrobial susceptibility of S. aureus and S. pseudintermedius, which are a major pathogens of public health concern in both animals and human beings. 132 ear swabs were collected from 92 dogs suffering with different types of ear infections. On isolation 85 (70.24%) isolates were identified as Staphylococcus. Through molecular profiling targeting nuc gene 23 isolates were identified as S. aureus, and 26 isolates were identified as S. pseudintermedius. On antimicrobial susceptibility testing S. aureus isolates exhibited greater sensitivity towards cephalothin (78.26%) followed by gentamicin and chloramphenicol (60.86% each), and ciprofloxacin (56.52%). S. pseudintermedius isolates exhibited greater sensitivity towards enrofloxacin (69.23%), followed by cephalothin and amoxiclav (61.53% each), and amikacin (57.69%). PCR studies targeting mecA, tetK, tetM genes revealed that 23 isolates of S. aureus and 26 isolates of S. pseudintermedius were positive for mecA gene. 14 isolates of S. aureus and 17 isolates of S. pseudintermedius were positive for tetK gene. 12 isolates of S. aureus, and 14 isolates of S. pseudintermedius were positive for tetM gene.